TRANSFORMASI TATA KELOLA SMKN MENJADI BERSTATUS BLUD DI JAWA BARAT - Imam Suseno; Heru Suparman; Chandra S. Haratua; Nurdin Nurdin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The transformation of vocational high schools into Regional Public Service Agencies (BLUD) is expected to make schools more independent, flexible, transparent, effective, and efficient. A number of SMKNs in West Java have been designated as BLUD since 2021. This study aims to determine whether the transformation of SMKN governance into BLUD status has an impact on the effectiveness and efficiency of SMKN BLUD performance in West Java. A descriptive quantitative research approach was used. Data were collected through questionnaires, group discussions, and document observation from 7 SMKN BLUD selected by simple random sampling. The analysis of BLUD management effectiveness used the Glickman quadrant, while the efficiency analysis used the DEA model utilizing the StataMp application. The analysis results indicate that governance is positioned in Quadrant II (effective), while 6 out of 7 BLUD vocational high schools are categorized as efficient. This efficiency is reflected in how inputs (students, teachers, and funding) are utilized to generate optimal performance outputs, such as industry partnerships, graduate employment, Tefa revenue, and teacher competency certification. Thus, the transformation of vocational high schools into BLUD status indicates an improvement in school performance in terms of effectiveness and efficiency. ABSTRAK Transformasi SMKN menjadi berstatus Badan Layanan Umum Daerah (BLUD) diharapkan sekolah menjadi lebih mandiri, fleksibel, transparan, berkinerja efektif dan efisien. Sejumlah SMKN di Jawa Barat ditetapkan menjadi BLUD sejak tahun 2021. Penelitian ini bertujuan untuk mengetahui apakah transformasi tata kelola SMKN menjadi berstatus BLUD berdampak efektifitas dan efisien kinerja SMKN BLUD di Jawa Barat. Menggunakan pendekatan penelitian kuantitatif deskriptif. Data dikumpulkan melalui kuesioner, forum group discussion, dan observasi dokumen dari 7 SMKN BLUD terpilih secara simple random sampling. Analisis efektifitas tata kelola BLUD menggunakan kuadran Glickman, sedangkan analisis efisiensi menggunakan model DEA memanfaatkan aplikasi StataMp. Hasil analisis menunjukkan bahwa tata kelola berada pada kuadran II (efektif), sementara 6 dari 7 SMKN BLUD tergolong efisien. Efisiensi tersebut tercermin dari pemanfaatan input (siswa, guru, dan pembiayaan) yang mampu menghasilkan output kinerja sekolah secara optimal, seperti kerja sama industri, penyerapan lulusan, pendapatan Tefa, dan sertifikasi kompetensi guru. Dengan demikian, transformasi SMKN menjadi berstatus BLUD menunjukkan adanya peningkatan kinerja sekolah yang lebih efektif dan efisien.